PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DAN PENILAIAN KINERJA TERHADAP TINGKAT PERPUTARAN KARYAWAN PT. AUTOMOBIL JAYA MANDIRI PABELAN SUKOHARJO - Agnyana, Handaru; Nurimansyah Setivia Bakti; Salma Rafsanjani Akbar (ITB AAS Indonesia Surakarta, 2025)
The employee turnover rate in a company is a separate problem that is considered very important to be addressed by a company. There are many factors that cause employee turnover. The higher the employee turnover rate, the lower the effectiveness and efficiency that occurs in an organization. In this study, leadership factors, work environment and performance are the main factors that will be observed. Based on observations that in this company, namely PT. Automobil Jaya Mandiri, there is a fairly high employee turnover rate every month. This is especially true in the sales department where there is often a very significant employee turnover every month. Leadership in this company is felt to need to be evaluated. A fairly good work environment also requires several evaluations to reduce employee turnover. Good performance evaluation is essential to reduce employee turnover.